Bond…(the Hegemonic Masculinity Of) James Bond - Martin Anthony , Paul C Cenizal (2015)
The mythology of James Bond is a pop culture phenomenon that is comparable to other such phenomena as Star Wars and Lord of the Rings, collectively creating a diverse selection of genres and archetypes. What most separates James Bond from the other two, perhaps, is its distinctly (hyper) masculine nature. A more controversial element of this mythology, however, is the equally popular “Bond girls.” From less-than-subtle names such as Chew Mee and Pussy Galore, to Bond actually being violent to these girls in earlier films, to instances such as the masseuse Dink having to leave Bond and Felix Leiter because the latter two had to have “man’s talk”, the barrage of criticism of the patriarchal leanings of the James Bond series is understandable. A critical reading of the Ian Fleming brainchild, as translated and adapted in five films from the franchise, its more popular medium, will be the framework for this journal article. The theories of feminism (and its various schools of thought) and commodification (in view of its five main elements) will be used as supplements to the main methodology to be used in the study, i.e., multimodal critical discourse analysis. Visual and linguistic cues will be prioritized in the analysis, but other such semiotic cues of significance will be included, as seen fit by the authors. Ultimately, the study will attempt to point out that a change in the tone, a mellowing down of the patriarchy, so to speak, of the more contemporary James Bond films is not necessarily the once hypermasculine anthology adapting a feminist stance, striving for equality of the sexes, in terms of portrayal on film. Rather, it will be the aim of the study to conclude whether it is societal pressure (specifically of a society trying to embrace diversity) or the emergence of a new model of hegemonic masculinity influencing the said change in tone of the James Bond films.